Molding Fabrication of High‐Energy Nanoparticles of Lead Azide Encapsulated by Graphene‐Doped Porous Carbon Matrix with Excellent Ignition Ability. Issue 10 (2nd August 2022) - Yan, Zhenzhan; Wang, Shuang; Yang, Li; Han, Jimin; Tong, Wenchao
Abstract: In this work, graphene oxide‐doped lead‐containing metal‐organic framework (BTC−Pb/GO) and polyvinyl alcohol were used as raw materials to prepare spherical or cylindrical lead azide composites by freeze‐drying, carbonization, and in‐situ azide steps. Nanoscale lead azide is uniformly distributed on the graphene‐doped porous carbon framework. Detailed characterization and testing show that LA/C/rGO exhibits excellent electrostatic sensitivity (1.94 J) and flame sensitivity (40 cm) due to the excellent electrical and thermal conductivity of porous carbon and graphene, which are superior to most of the previously reported modified lead azide. Abstract :